Perancangan Sistem Informasi Pelayanan Kesehatan UPTD Puskesmas XYZ - Dudi Awalludin; Agustin Eka Wulandari (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2020)
The UPTD Puskesmas XYZ is one of the first-level health service centers that served 1034 patients in December 2016. To do so much data processing is still done manually, starting from registration to recording medical records (RM). Management of patient data and medical records still uses forms to register and record patient data of 1034 patients in December 2016. Seeing the burden of the registration section in recording registration and searching of patient data and searching for Kartu Status Pasien (KSP) must be done manually. The Waterfall Model is one of the models in the development of the system, starting with the stages of data collection using the method of observation, interviews, literature study, and documentation studies of the running system. The next stage is system design, the tools used are flowcharts, Entity Relationship Diagrams (ERD), and Data Flow Diagrams (DFD). Health service system design web based is expected to built a system to assist the registration in facilitate the search for patient data and management from patient data to medical record quickly, precisely and accurately.